Cinema as The “weapon of The enemy”: The archaeology of an islamist film criticism discourse - BOSTAN, MESUT; MUSTAFA, SÜHEYLA NİL (My University, 2022)
The issue of how cinema should be, the influence of which on the society was indisputable for the intellectuals, became an important subject during especially 1960s in Turkey. During these years, the discourse of Islamism once again made an appearance in Turkish politics and thought in the form of a nationalist religious discourse. This study will examine the reproduction process of Islamist discourse on cinema and analyze the composition of Islamist film criticism. Even though the discourse of film criticism expressed as “arming up with the weapon of the enemy” seemed to come forward with its rejectionist attitude, it actually reflected an attitude toward harmony beyond measure. Redescribing cinema as an area dominated by symbolic violence caused the amorphization and reactiveness of cinema products. On the other hand, a second direction that opened a door for the imitation of the cinematic movements and products considered as rivals brought along the state of being bereft of identity despite its heavy emphasis on identity. The idea of “arming up with the weapon of the enemy” showed a continuity in the perception of cinema as a propagandist and political instrument. It became functional as a discourse activated by Islamists before they entered into the fields such as cinema production and film criticism, fields that were new to them. This understanding is based on a modernization-oriented approach that envisages a rupture with the tradition and distinguishing oneself from the existing cultural accumulation. It produces the content of this understanding by translating the dominant thoughts in the area on which it would like to exert its dominance into religious terminology. In that regard, it is a product of a mimetic cultural stance.

Türkiye’de özellikle 1960’lı yıllarda aydınlar için toplum üzerindeki etkisi tartışılmaz olan sinemanın nasıl olması gerektiği önemli meselelerden biri haline gelmiştir. Bu yıllarda İslamcılık söylemi milliyetçi mukaddesatçı bir biçimde yeniden Türk siyasetinde ve düşünce hayatında arzı endam etmiştir. Bu çalışmada sinemaya dair İslamcı söylemin yeniden üretilmesi süreci ele alınacak olup İslamcı sinema eleştirisi söyleminin kompozisyonu analiz edilecektir. “Düşmanın silahıyla silahlanma” şeklinde ifade bulan sinema eleştirisi söylemi reddiyeci tutumuyla öne çıkıyor gibi görünse de aslında ölçüsüz bir uyum tavrını yansıtmaktadır. Sinemayı sembolik şiddetin hâkim olduğu bir alan olarak yeniden tanımlamak sinema ürünlerinin de şekilsizleşmesine ve tepkiselleşmesine sebep olmuştur. Diğer yandan rakip görülen sinema akım ve ürünlerini taklide kapı açan ikinci bir yön yoğun kimlik vurgusuna rağmen kimliksizleşmeyi de beraberinde getirmiştir. “Düşmanın silahıyla silahlanma” düşüncesi sinemanın propaganda ve siyaset aracı olarak algılanmasında bir süreklilik gösterir. İslamcıların özellikle sinema yapımı, sinema eleştirisi gibi kendileri için yeni olan alanlara girmeden önce aktif hale getirdikleri bir söylem olarak işlevselleşmiştir. Genel manasıyla gelenekten kopuşu ve mevcut kültürel birikimden kendini ayrıştırmayı öngören modernleşmeci bir tasavvura dayanır. Bu tasavvurun içeriğini de iktidar elde edilmek istenen alana hâkim olan düşünceleri dini terminolojiye tercüme ederek üretir. Bu açıdan mimetik bir kültürel tavrın ürünüdür.
“Düşmanın silahı” olarak sinema: İslamcı bir sinema eleştirisi söyleminin arkeolojisi
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Turkish Cinema; Sociology of Cinema; Islamism; Film Criticism; History of Cinema; Türk Sineması; Sinema Sosyolojisi; İslamcılık; Sinema Eleştirisi; Sinema Tarihi